INCREASING THE STRENGTH OF LIGHTWEIGHT CONCRETE AND RESEARCH OF BEAM STRUCTURES MADE FROM IT - Zohitjon Inomov Zokirjonovich; S.J.Razzaqov (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article examines methods for increasing the strength of lightweight concrete and the performance characteristics of beam structures made from it. During the research, the effect of various admixtures and modifying additives on the mechanical properties of concrete was studied. Based on the results of experimental tests and computer modeling, the possibilities of creating load-bearing structures based on lightweight concrete were assessed. Nowadays, increasing the strength of lightweight concrete and using structures made from it in modern constructions is being discussed. Opinions are given on increasing the strength of lightweight concrete and using beam structures made from it. The bulk density, thermal conductivity, and strength of lightweight concrete depend primarily on the properties of the fillers added to it, the amount of water added to the mixtures, and the brand of cement. In the preparation of lightweight concrete structures, the mixture is often placed in molds in a virgin state.